609. MINIMALLY INVASIVE CERVICAL ESOPHAGECTOMY (MICE): FIRST RESULTS OF A DUTCH PILOT STUDY. (24th September 2022) - van Veenendaal, LM; Vercoulen, RJMT; Shiozaki, A; Fujiwara, H; Rosman, C; Klarenbeek, BR
Abstract: Surgical resection remains the cornerstone of curative treatment for patients with esophageal cancer. Transthoracic minimally invasive esophagectomies have reduced the occurrence of pulmonary complications, however it is still associated with significant morbidity. The Minimally Invasive Cervical Esophagectomy (MICE) is a novel surgical technique. To date this technique is not routinely performed in European esophageal cancer patients. We aim to assess the safety and efficacy of the MICE procedure in Dutch patients with esophageal carcinoma. The MICE is a recently developed surgical technique in Japan. The procedure combines a laparoscopic transhiatal and single-port transcervical mediastinal dissection and aims to ensure a radical oncological resection with a reduction of pulmonary complications because a thoracotomy/scopy is avoided. A prospective pilot study was performed including consecutive patients undergoing MICE for esophageal cancer. Twenty patients were included. The male/female ratio was 16:4 with a median age of 71 years (IQR 52-85). Median operation time and blood loss was 350 minutes (IQR 326-360) and 100 ml (IQR 50-175). Conversion occurred in five patients (20%). Recurrent laryngeal nerve paralysis was seen in seven patients (35%), at least six of which were temporary. Anastomotic leakage occurred in three patients (15%, 2 ECCG grade 1 and 1 ECCG grade 3). Pneumonia, chyle leakage and hemothorax all occurred once in different patients (Clavien-Dindo grade 2, 4 and 3a, respectively). The median length-of-stay was 10 days (IQR 7-10). MICE is a novel minimally invasive surgical technique which seems safe and effective to perform in Dutch patients with esophageal carcinoma. As expected, a higher incidence of RLNP was seen, in most cases only temporarily. Long-term safety and effectiveness will be prospectively evaluated in a larger population.